FISHERIES OF MALWAN - Kaikini, A S (Indian Journal of Fisheries, 2016)
MALWAN is one of the important fishing centres on the west coast and itis situated at almost the northern limit up to which the exploitation of theeconomically important mackerel and oil-sardine fisheries of the west coastextends. In spite of its importance there is hardly any information on thefisheries of this place; and the present work was undertaken with a viewto fill this gap in our knowledge of the conditions existing in the major fishingcentres of the west coast. The following pages give the result of the fisherysurvey work carried on at Malwan for a period of six years from 1950 to1957 (with a gap during 1953 and 1954 when no data w:re collected). Incomputing the data the "random sampling" method was used for estimatingthe total catch, unit-effort, etc.